2017
DOI: 10.5455/medarh.2017.71.270-273
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hypothyreoidism after Radioactive Iodine-I131 Treatment in Dependance of Hyperthyreoidism Etiology and Therapy Dose

Abstract: Introduction:Consensus hasn’t been yet achieved about optimal dose quantity that could prevent post therapy hypothyroidism, thus dosing approach varies among different centers. I131 doses can be fixed or calculated, although treatment outcomes don’t differ significantly according to recent acknowledgments.Aim:Determination of the incidence of hypothyroidism after radioiodine treatment (I131) in dependence of hyperthyroidism etiology and quantity of applied doses.Materials and methods:The study included 100 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
2
8
1
Order By: Relevance
“…Our study showed that the average age of the patients was 45.07 ± 12.59 years and the ratio of male to female was 1:4.78, which was similar to the previous reports. In the literatures, the incidence of hypothyroidism after RAI therapy ranged from 8.5 to 90% [20][21][22][23][24]. Our results indicated that the early hypothyroidism occurred in 218 (69.87%) patients, and only nine patients (2.88%) achieved euthyroidism, which was consistent with a recent study conducted in Singapore [25].…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that the average age of the patients was 45.07 ± 12.59 years and the ratio of male to female was 1:4.78, which was similar to the previous reports. In the literatures, the incidence of hypothyroidism after RAI therapy ranged from 8.5 to 90% [20][21][22][23][24]. Our results indicated that the early hypothyroidism occurred in 218 (69.87%) patients, and only nine patients (2.88%) achieved euthyroidism, which was consistent with a recent study conducted in Singapore [25].…”
Section: Discussionsupporting
confidence: 91%
“…A higher dose-1 has imparted euthyroid outcome in patients with female gender, GD,or the receiver of two instances of RAIT in this series. This fact is unique and draws attention to some reported determinants of post-RAIT hypothyreosiswhich are female gender and administered dose > 600 MBq (>16.21 mCi), (19).The incidences of post-RAIT hypothyreosis from GD, STN and MNG were 61%, 67% and 35%in the current serieswhile those from another 3-years series were 89.5%, 26.8% and 57.1% respectively (20). Thus the goal of attaining hypothyroidism by RAIT in patients with GD and STN (21) was successful in this series with the rest remained euthyroid, indicating favorable treatment outcome which in turn indicates the appropriate standard of institutional practice.…”
Section: Discussionmentioning
confidence: 54%
“…In some respects, this bilateral symmetrical pattern of uptake is similar to the situation in Graves' disease in people, where the hyperplastic thyrocytes of both thyroid lobes take up 131 I diffusely and hypothyroidism is almost inevitable. 28 , 29 , 42 Our observation that cats with an asymmetrical (heterogeneous) 99m TcO 4 − uptake pattern were less likely to develop 131 I‐induced hypothyroidism likely relates to the lower radiation dose delivered to the thyroid nodule with less intense 131 I uptake, which may help preserve more of the dormant or normal thyrocytes within that adenomatous lobe.…”
Section: Discussionmentioning
confidence: 94%